2002
DOI: 10.2337/diacare.25.4.672
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Women With Type 1 Diabetes

Abstract: OBJECTIVE -This study aimed to 1) examine the prevalence of sexual problems in women with type 1 diabetes, 2) compare this prevalence rate with that of an age-matched control group, 3) study the influence of diabetes-related somatic factors on female sexuality, and 4) study the influence of psychological variables on the sexual functioning of both groups. RESEARCH DESIGN AND METHODS-A total of 120 women with diabetes visiting the outpatient diabetes clinic completed questionnaires evaluating psychological adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
230
5
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(269 citation statements)
references
References 25 publications
(41 reference statements)
25
230
5
5
Order By: Relevance
“…43) Diabetes also results reproductive disorders that results male and female infertility. 1,2) The present work confirm the male reproductive disorders in diabetic state as proposed by others 44) along with protective effect of the formulated experimental drug, MTEC for recovery of diabetes and testicular dysfunctions noted in diabetic state. The aqueous-methanol (40 : 60) extract of the above plant parts used here exhibit most effective and performing results than other solvents used for extract preparation which has been noted by trial and error by our labora- tory.…”
Section: Discussionsupporting
confidence: 75%
“…43) Diabetes also results reproductive disorders that results male and female infertility. 1,2) The present work confirm the male reproductive disorders in diabetic state as proposed by others 44) along with protective effect of the formulated experimental drug, MTEC for recovery of diabetes and testicular dysfunctions noted in diabetic state. The aqueous-methanol (40 : 60) extract of the above plant parts used here exhibit most effective and performing results than other solvents used for extract preparation which has been noted by trial and error by our labora- tory.…”
Section: Discussionsupporting
confidence: 75%
“…Also for diabetes mellitus, which represents an important causes of ED in men, 60 the data about the prevalence of FSD are controversial. [61][62][63] We found 64 a negative relationship between body weight and sexual function in 52 women with abnormal values of FSFI (score p23) (Figure 2). We also showed that obesity affects several aspects of sexual function in otherwise healthy women with FSD, including arousal, lubrication, satisfaction and orgasm, but not desire and pain.…”
Section: Obesity Metabolic Syndrome and Female Sexual Functionmentioning
confidence: 99%
“…14 Also for diabetes mellitus, which represents an important causes of erectile dysfunction in men, 15 the data about the prevalence of FSD are controversial. 16,17 Our study design has several strengths and weaknesses. (1) We did a case-control study across a wide range of body weight and including both premenopausal and postmenopausal women; so, it was not limited by the more prevalent sexual dysfunction in menopause.…”
Section: Discussionmentioning
confidence: 99%